2011
DOI: 10.1089/gtmb.2010.0118
|View full text |Cite
|
Sign up to set email alerts
|

Association of Methylene Tetrahydrofolate Reductase C677T Genotype With Type 2 Diabetes Mellitus Patients With and Without Renal Complications

Abstract: Diabetes is gradually getting the status of a global epidemic, with India projected as the capital of type 2 diabetes mellitus (T2DM). Nephropathy is an important complication of diabetes and a major cause of end-stage renal disease. Studies from different parts of the world have given controversial results regarding the association of methylene tetrahydrofolate reductase (MTHFR) gene variation with T2DM and diabetic nephropathy (DN). This case-control study assessed the association of MTHFR C677T mutation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 26 publications
0
15
1
2
Order By: Relevance
“…The relationship between the MTHFR C677T polymorphism and T2D risk has been explored in many previous studies, with some indicating positive association [5,7,22,26], whereas others reported null association [21,23,24,25]. A number of factors may contribute to the discrepancy between prior studies, such as ethnic genetic differences and dietary habits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between the MTHFR C677T polymorphism and T2D risk has been explored in many previous studies, with some indicating positive association [5,7,22,26], whereas others reported null association [21,23,24,25]. A number of factors may contribute to the discrepancy between prior studies, such as ethnic genetic differences and dietary habits.…”
Section: Discussionmentioning
confidence: 99%
“…Cooccurrence with the MTRR A66G polymorphism may aggravate the adverse effect of the MTHFR C677T polymorphism on plasma Hcy level [20]. Some studies have assessed the relationship between the MTHFR C677T polymorphism and T2D, with most showing a significant positive association [5,7,21,22,23,24,25,26]. Mechanisms linking HHcy with T2D are not clearly understood, and one of them may be insulin resistance [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…22 Movva et al determined that the MTHFR C677T allele confered a four-fold risk of developing type-2 diabetes mellitus in their study on 236 diabetic patients and 100 control individuals. 23 An increase in mean serum Hcy concentrations in women with polycystic ovarian syndrome, another clinical condition associated with insulin resistance, has also reported. 24 In addition, Schachter et al previously reported that insulin resistance and hyperinsulinaemia in patients with PCOS is associated with elevated plasma Hcy levels regardless of body weight.…”
Section: Discussionmentioning
confidence: 91%
“…В этой связи отметим, что в исследовании, проведенном по типу «случай -контроль» в Китае и Индии, была выявлена ассоциация аллеля Т это-го полиморфизма с высоким уровнем гомоцистеи-на, сахарным диабетом 2-го типа и нефропатоло-гией, осложняющей течение данного заболевания [6][7][8][9].…”
Section: обсуждение и заключениеunclassified
“…Результаты популяционных исследований по-казали, что полиморфизм rs1801133 гена MTHFR ассоциирован с увеличением риска формирова-ния дефекта нервной трубки у плода, развития сердечно-сосудистых заболеваний, сахарного диа-бета 2-го типа и остеопороза [6][7][8][9]. Частота встре-чаемости аллеля Т в европейских популяциях со-ставляет 30-33% [6,10].…”
unclassified